Association of High-Risk Drinking with Metabolic Syndrome and Its Components in Elderly Korean Men: The Korean National Health and Nutrition Examination Survey 2010–2012 - Kim, Ji-Hyun (Korean J Fam Med, 2018)
BACKGROUND: Previous studies have examined the association between alcohol consumption and metabolic syndrome (MetS) in adults, but studies in the elderly are lacking. We examined the relationship between high-risk alcohol consumption and MetS in elderly Korean men using the Alcohol Use Disorders Identification Test (AUDIT) questionnaire from the 2010–2012 Korean National Health and Nutrition Examination Survey. METHODS: Among 25,534 subjects, 2,807 were men >60 years of age; after exclusions, we included 2,088 men in the final analysis. We categorized the study participants into three groups according to AUDIT score: low risk (0–7), intermediate risk (8–14), and high risk (≥15 points). RESULTS: Among the study population, 17.0% of the men were high-risk drinkers, who had the highest mean waist circumference, systolic and diastolic blood pressure (BP), fasting plasma glucose (FPG), and triglyceride (TG) levels. The overall prevalence of MetS was 41.9% in the elderly men, and it was significantly higher in the group with high (48.3%) versus low (31.9%) AUDIT scores. The prevalence of MetS components (elevated BP, high FPG, high TG, and low high-density lipoprotein cholesterol) was associated with a high AUDIT score. The odds ratios (95%confidence interval) of the high-risk group for MetS, elevated BP, and high TG were 1.40 (1.03–1.89), 1.82 (1.28– 2.60), and 1.77 (1.30–2.41) after adjustment for confounding variables. CONCLUSION: AUDIT score was correlated with most MetS components in elderly Korean men.